(3GdOhQ GdShSjh(B-(3GbJUGOj ddeDSSGJ GdfGTFI aj OYe NWW GdJfejI GdeSJOGeI (B/s - (3adGb, eMeOs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2022)
(3MhceI GdTQcGJ GdfGTFI, GdHjFI GdQjGOjI GdeJfGejI ddeDSSGJ GdfGTFI hGfYcGSGJgG Ydi GdLGfH GdShSjh(B-(3GbJUGOj(B: (3Jbjje GdaQU hGdJMOjGJ aj GdeedcI GdYQHjI GdSYhOjI, GdeSDhdjI GdGLJeGYjI ddebGhdGJ aj EWGQ GdJhLg fMh GdGSJOGeI,CgejI GdMhceI hOhQgG aj JaYjd feh GdeDSSGJ GdfGTFI, MGdI GdeDSSGJ GdfGTFI aj GdLRGFQ, aGYdjI JWHjb HQGeL GdeSDhdjI GdGLJeGYjI hOhQgG aj GSJeQGQjI GdeDSSGJ GdfGTFI hJWhjQgG bQGAI ShSjhdhLjI JMdjdjI, GdeSDhdjI GdHjFjI hGdGLJeGYjI eONd deSGgeI GdeDSSGJ GdfGTFI aj JMbjb GdJfejI GdeSJOGeI, MGdI GdLRGFQ(B....s
(3eQGLY U(B.397 - (3cJGH LeGYj deLehYI ef GdeDdajf(B.s
Keywords: (3GdJfejI GdGbJUGOjIs